DIGITAL ECONOMY - AS AN IMPORTANT FACTOR IN THE DEVELOPMENT OF DIFFERENT SECTORS OF SOCIETY (Conference Zone, 2022)
The article scientifically analyzes that the development of the digital economy is an important factor in the development of various sectors of society. It was also taken into account that innovation is a tangible result of the introduction of capital into new equipment or technology, new forms of organization of production, labor, services and management, including new forms of control and accounting, methods of planning and analysis.